2018
DOI: 10.4041/kjod.2018.48.6.395
|View full text |Cite
|
Sign up to set email alerts
|

Association between genetic polymorphisms and external apical root resorption: A systematic review and meta-analysis

Abstract: ObjectiveTo date, only a few studies have investigated the relationships between genetic polymorphisms and external apical root resorption (EARR). Hence, the aim of this systematic review was to explore the relationship between different gene polymorphisms and their association with EARR.MethodsA complete literature search was conducted by two independent reviewers. The PubMed, Science Direct, and Scopus databases were searched. In addition, the bibliographies of all textbooks and relevant articles were search… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In addition, it is important to consider that the inherent characteristics of each study population may interfere with the EARR process, since differences in the frequency of EARR as well as in the risk factors associated with EARR among populations have already been described in the literature 8. Recent studies also reported a genetic predisposition that may explain why one patient is more likely to develop EARR during orthodontic treatment than does another2829; therefore, individual variability should also be considered, even though it has not been evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is important to consider that the inherent characteristics of each study population may interfere with the EARR process, since differences in the frequency of EARR as well as in the risk factors associated with EARR among populations have already been described in the literature 8. Recent studies also reported a genetic predisposition that may explain why one patient is more likely to develop EARR during orthodontic treatment than does another2829; therefore, individual variability should also be considered, even though it has not been evaluated in the present study.…”
Section: Discussionmentioning
confidence: 99%
“… 2 However, a recent meta-analysis suggested that the IL-1β polymorphism is not correlated with a predilection to EARR. 3 Earlier literature showed that the incidence and severity of root resorption was connected with numerous mechanical factors, including force magnitude, the amount or distance of tooth movement, force type, and treatment appliance. 4 , 5 Increased treatment time or prolonged treatment duration positively correlated with increased EARR 4 ; thus, shortening the treatment duration is a worthwhile goal as it could decrease the risk of EARR.…”
Section: Introductionmentioning
confidence: 99%
“…Orthodontically induced root resorption (OIRR) is a frequent iatrogenic effect of orthodontic intervention (Abass et al, 2008; Hartsfield, Everett, & Al‐Qawasmi, 2004). In this process, undesirable activities of specific resorptive cells on the root surface result in resorption of cementum and dentin (Nowrin et al, 2018; Weltman, Vig, Fields, Shanker, & Kaizar, 2010). If handled improperly, OIRR may compromise treatment outcome and even the longevity of the tooth.…”
Section: Introductionmentioning
confidence: 99%